Social Science Material Development Design Space-Time-Values Dimensions to Improve 21st Century Life Skills - Deny Setiawan; Julia Ivana; Sri Yunita; Hidayat Hidayat (Randwick International of Social Science Journal, 2022)
This development research aims to produce a design for the development of Social Science materials with space-time-values ​​dimensions to improve 21st century life skills among students of the Faculty of Social Sciences, Universitas Negeri Medan. The specific target to be achieved is the production of a Social Science Material Development textbook with the Space-Time-Values ​​Dimension. The research method used is the R&D method following the Borg & Gall procedure. The research subjects involved: lecturers who teach courses; students as subjects for a limited group trial; and five experts for textbook validation. The instruments used were expert validation questionnaires, learning outcomes tests and observation sheets which were analyzed using qualitative descriptive analysis to analyze information on various field conditions; quantitative descriptive analysis used to analyze the scores given by the expert; and statistical analysis assisted by STATCAL software. The result of the research shows that the textbook for the Development of Social Science Materials with the dimensions of space-time-values ​​was developed, valid and suitable for use. Other findings based on observations show that the design of textbook material development contributes to students' 21st century life skills in aspects: critical thinking and problem solving, creative and innovative, communication skills, and collaboration skills.